Simultaneous observations of optical lightning from space and LF band lightning waveforms from the ground. Issue 2 (25th January 2017) - Kikuchi, Hiroshi; Sato, Mitsuteru; Ushio, Tomoo; Morimoto, Takeshi; Kikuchi, Masayuki; Yamazaki, Atsushi; Suzuki, Makoto; Ishida, Ryohei; Sakamoto, Yuji; Wu, Ting; Kawasaki, Zen
Abstract: Observations of optical lightning data with a photometer (PH4) at wavelengths of 599–900 nm on the International Space Station were conducted simultaneously with observations of low‐frequency (LF) electromagnetic waves with a ground‐based LF lightning locating system. The relationship between the PH4 light curve and electromagnetic waveforms in the LF band was examined for 11 lightning events. The PH4 sensor detected a small optical change even for weak light emitted from lightning discharges in clouds, including preliminary breakdown. Particularly, return strokes, including subsequent return strokes, showed a clear relationship between radiated LF waves and optical waveforms. For negative return strokes, we found a clear correlation between the absolute optical intensity and peak current. The slope of the regression line is 9.7 × 10 −8  kA W −1 with an intercept of 9.9 kA. Key Points: Simultaneous observations of optical lightning data and LF electromagnetic waves were conducted The optical sensor mounted on the ISS detected the weak light emitted from lightning discharges in clouds such as preliminary breakdown For negative return strokes, the absolute optical intensity and peak current show a clear correlation